Primary school pre-service teachers’ technology self-efficacy in creating e-learning content using CourseLab 2.4 - Theresia Yunia Setyawan (Universitas Negeri Yogyakarta, 2019)
This was descriptive research aiming at providing a general description of primary school pre-service teachers’ technology self-efficacy in creating e-learning content using CourseLab 2.4. The main instrument of this research was a self-report questionnaire consisting of both scaled and free-response items. The questionnaire was distributed to 46 sophomores of Primary School Teacher Education Program of Sanata Dharma University taking Media Pembelajaran Berbasis ICT (MPB ICT) course as one of their compulsory courses. The analysis of the data gathered from the questionnaire responses showed that 58.7% of the primary school pre-service teachers of Sanata Dharma University had ‘average’ technology self-efficacy in creating e-learning content using CourseLab 2.4 while only 41.3% having ‘high’ self-efficacy in using the same software. The average technology self-efficacy was attributed to their unfamiliarity to the authoring software and their limited experience in course content development as well as in coding in general. The student teachers, however, credited the software for providing them with tools and machinery to create their own tests or quizzes for any learning materials they had previously created.Keywords: Pre-service teachers, primary school, self-efficacy, CourseLab 2.4